Formation of a quasi-solid structure by intercalated noble gas atoms in pores of CuI-MFU-4l metal–organic framework. Issue 4 (24th November 2014) - Magdysyuk, Oxana V.; Denysenko, Dmytro; Weinrauch, Ingrid; Volkmer, Dirk; Hirscher, Michael; Dinnebier, Robert E.
Abstract : Ten crystallographically different positions for Xe and eight positions for Kr form a quasi-solid structures within the large-pore metal–organic framework Cu I -MFU-4 l . Abstract : The primary adsorption sites for Kr and Xe within the large-pore metal–organic framework Cu I -MFU-4 l have been investigated by high-resolution synchrotron powder diffraction, revealing an enormous number of adsorption sites: in total, 10 crystallographically different positions for Xe and 8 positions for Kr were localized, the first five of which are located near metal atoms and the organic linker, and the remaining sites form a second adsorption layer in the pores.